Nomophobia Education and Counseling in Teenagers Self-Controlling as Prevention of Gadget Addiction at SMA Negeri 21 Makassar - Kadek Ayu Erika; Nur Fadilah; Suni Hariati; Ariyanti Saleh; Arnis Puspita R; Istiana Tajuddin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
No Mobile Phone Phobia (Nomophobia) is excessive anxiety/fear when away from smartphones caused by several conditions such as no battery and running out of quota. Nomophobia can be detrimental to adolescents during their school years such as decreased achievement, physical problems (pain in certain body parts), and psychological (panic especially when away from their smartphones). The importance of Nomophobia education and counseling activities can control themselves to use smartphones wisely. The purpose of the service is to educate adolescents of SMA Negeri 21 Makassar so that they do not experience Nomophobia tendencies. The results of the service on 121 adolescents, obtained that most respondents were 16 years old and used smartphones for> 2 hours. The most self-control in the good category (77.7%) and the tendency of Nomophobia in the moderate category (77.7%), There is a difference in the level of knowledge during the pre-post test after education, namely p = 0.0001. Education must be given to teenagers involving parents and schools to increase understanding of Nomophobia as a preventive measure as well as the involvement of health workers in identifying and intervening for teenagers who have high levels of Nomophobia.